An observational study on benign breast diseases in a tertiary healthcare centre in Chengalpettu district - R., Anusha; Balaji, D. (International Surgery Journal, 2022)
Background: Benign breast disorders constitute the majority of breast complaints presented by young females to a surgical OPD. It is 10 times more common than cancerous conditions and deserves attention due to its high prevalence, impact on woman’s life associated anxiety and possibility of some turning into cancerous conditions. It is divided into aberrations and abnormalities in development, epithelial and stromal proliferations, inflammations and neoplasms. In this study we aim at finding the prevalence, age, clinical presentation of commonest benign breast conditions and its correlation with pathological and radiological studies. Methods: The 98 cases of benign breast diseases between the age group of 15-45 years underwent triple assessment consisting of clinical examination, ultrasonography and fine needle aspiration cytology. Patients who were diagnosed with malignancy were excluded from the study. Results: Out of 98 breast lesions the commonest presentation was breast lump and found most commonly in right upper quadrant. The most common age was 20-30 years and fibroadenosis was most common benign lesion followed by fibroadenoma, mastalgia, breast abscess and nipple discharge. Conclusions: BBDS are a common problem among females in the reproductive age group. It is important to differentiate between fibroadenoma and fibroadenosis. FNAC and ultrasonography are a useful aid in diagnosis of benign breast lesions.